2020
DOI: 10.1155/2020/8021920
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Oxindoles and Determination of Their Antibacterial Properties

Abstract: A versatile method for the synthesis of new oxindoles was developed by the reaction between substituted isatins and 5-aminopyrazoles. The reaction was carried out at room temperature in ethanol using p-toluenesulfonic acid as the catalyst. The products were obtained with acceptable to excellent yields (44–96%). Structures of the new compounds were unambiguously established by spectroscopic and analytical techniques. The antibacterial activity was determined by microdilution assays. Compounds 3b, 3e, and 3g sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
2
0
2
Order By: Relevance
“…Furthermore, pyrazole heterocycle is pharmaceutically important that has been explored as a potential chemotherapeutic agent in medicinal chemistry [15][16][17][18][19][20][21][22][23]. Recently, Pablo et al reported that 3-(4-Pyrazolyl)oxindoles obtained by reaction of 5-aminopyrazoles with isatins possess potent antibacterial properties [24]. Figure 1 shows the selective representative examples of compounds containing bioactive 3-hydroxy-2-oxindoles and pyrazole.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, pyrazole heterocycle is pharmaceutically important that has been explored as a potential chemotherapeutic agent in medicinal chemistry [15][16][17][18][19][20][21][22][23]. Recently, Pablo et al reported that 3-(4-Pyrazolyl)oxindoles obtained by reaction of 5-aminopyrazoles with isatins possess potent antibacterial properties [24]. Figure 1 shows the selective representative examples of compounds containing bioactive 3-hydroxy-2-oxindoles and pyrazole.…”
Section: Introductionmentioning
confidence: 99%
“…The scaffold possesses diverse biological activities including anti-inflammatory (1), anticonvulsant (2), antidepressant (3), antiallergic (4), antitubercular (5), antidiabetic (6), antiviral (7) and antimicrobial activity (8)(9)(10)(11). Oxindole and other related ring systems also exhibit several biological activities (12)(13)(14)(15). Thiosemicarbazone derivatives of indoline-2,3-dione show appreciable antifungal, antibacterial and antiviral activities in vivo and in vitro (16).…”
mentioning
confidence: 99%
“…As substituições nas diferentes posições como C-3, NH e hidrogênios do anel aromático por diversos grupos funcionais, levam a atividades biológicas diversificadas. [54][55][56][57][58][59][60][61][62] Alguns exemplos de oxindóis que exibem atividades biológicas interessantes são representados na Figura 3. O Nintedanib (xlviii) é um inibidor da tirosina quinase de múltiplos receptores.…”
Section: Relevância Do Núcleo Oxindolunclassified
“…60 Por outro lado, o composto (lii) foi avaliado quanto à atividade antibacteriana contra Staphylococcus aureus, mostrando-se um candidato com atividade antiestafilocócica promissora. 61 Ainda, o oxindol (liii) exibiu excelente atividade antitubercular in vitro contra a cepa H37Rv de Mycobacterium tuberculosis. 62…”
Section: Síntese De Azaheterociclos Via Carbamoilação/ciclização Tandemunclassified